Difference between revisions of "2018 AIME I Problems/Problem 5"

m (Solution)
Line 3: Line 3:
 
For each ordered pair of real numbers <math>(x,y)</math> satisfying <cmath>\log_2(2x+y) = \log_4(x^2+xy+7y^2)</cmath>there is a real number <math>K</math> such that <cmath>\log_3(3x+y) = \log_9(3x^2+4xy+Ky^2).</cmath>Find the product of all possible values of <math>K</math>.
 
For each ordered pair of real numbers <math>(x,y)</math> satisfying <cmath>\log_2(2x+y) = \log_4(x^2+xy+7y^2)</cmath>there is a real number <math>K</math> such that <cmath>\log_3(3x+y) = \log_9(3x^2+4xy+Ky^2).</cmath>Find the product of all possible values of <math>K</math>.
  
==Solution==
+
==Solution 1==
 
Using the logarithmic property <math>\log_{a^n}b^n = \log_{a}b</math>, we note that <math>(2x+y)^2 = 4x^2+4xy+y^2</math>.  
 
Using the logarithmic property <math>\log_{a^n}b^n = \log_{a}b</math>, we note that <math>(2x+y)^2 = 4x^2+4xy+y^2</math>.  
 
That gives <math>x^2+xy-2y^2=0</math> upon simplification and division by <math>3</math>. Then, <math>x=y</math> or <math>x=-2y</math>.
 
That gives <math>x^2+xy-2y^2=0</math> upon simplification and division by <math>3</math>. Then, <math>x=y</math> or <math>x=-2y</math>.
Line 13: Line 13:
  
 
The cases <math>x=y</math> and <math>x=-2y</math> can be found by SFFT ([https://artofproblemsolving.com/wiki/index.php/Simon%27s_Favorite_Factoring_Trick Simon's Favorite Factoring Trick]) from <math>x^2+xy-2y^2=0 \implies (x+2y)(x-y)=0</math>.
 
The cases <math>x=y</math> and <math>x=-2y</math> can be found by SFFT ([https://artofproblemsolving.com/wiki/index.php/Simon%27s_Favorite_Factoring_Trick Simon's Favorite Factoring Trick]) from <math>x^2+xy-2y^2=0 \implies (x+2y)(x-y)=0</math>.
 +
==Solution 2==
 +
Do as done in Solution 1 to get <math>x^2+xy-2y^2=0\implies (\frac{x}{y})^2+\frac{x}{y}-2=0\implies \frac{x}{y}=\frac{-1\pm\sqrt{1+8}}{2}=1,-2</math>. Do as done in Solution 1 to get <math>9x^2+6xy+y^2=3x^2+4xy+Ky^2\implies 6x^2+2xy+(1-K)y^2=0\implies 6(\frac{x}{y})^2+2\frac{x}{y}+(1-K)=0\implies \frac{x}{y}=\frac{-2\pm \sqrt{4-24(1-K)}}{12}\implies \frac{x}{y}=\frac{-2\pm 2\sqrt{6K-5}}{12}=\frac{-1\pm \sqrt{6K-5}}{6}</math>. If <math>\frac{x}{y}=1</math>, then <math>1=\frac{-1\pm \sqrt{6K-5}}{6}\implies 6=-1\pm \sqrt{6K-5}\implies 7=\pm \sqrt{6K-5}\implies 49=6K-5\implies K=9</math>. If <math>\frac{x}{y}=-2</math>, then <math>-2=\frac{-1\pm \sqrt{6K-5}}{6}\implies -12=-1\pm \sqrt{6K-5}\implies -11=\sqrt{6K-5}\implies 121=6K-5\implies 126=6K\implies K=21</math>. Hence our final answer is <math>21\cdot 6=\boxed{126}</math>
 +
-vsamc
  
 
==See Also==
 
==See Also==
 
{{AIME box|year=2018|n=I|num-b=4|num-a=6}}
 
{{AIME box|year=2018|n=I|num-b=4|num-a=6}}
 
{{MAA Notice}}
 
{{MAA Notice}}

Revision as of 14:51, 12 April 2020

Problem 5

For each ordered pair of real numbers $(x,y)$ satisfying \[\log_2(2x+y) = \log_4(x^2+xy+7y^2)\]there is a real number $K$ such that \[\log_3(3x+y) = \log_9(3x^2+4xy+Ky^2).\]Find the product of all possible values of $K$.

Solution 1

Using the logarithmic property $\log_{a^n}b^n = \log_{a}b$, we note that $(2x+y)^2 = 4x^2+4xy+y^2$. That gives $x^2+xy-2y^2=0$ upon simplification and division by $3$. Then, $x=y$ or $x=-2y$. From the second equation, $9x^2+6xy+y^2=3x^2+4xy+Ky^2$. If we take $x=y$, we see that $K=9$. If we take $x=-2y$, we see that $K=21$. The product is $\boxed{189}$.

-expiLnCalc

Note

The cases $x=y$ and $x=-2y$ can be found by SFFT (Simon's Favorite Factoring Trick) from $x^2+xy-2y^2=0 \implies (x+2y)(x-y)=0$.

Solution 2

Do as done in Solution 1 to get $x^2+xy-2y^2=0\implies (\frac{x}{y})^2+\frac{x}{y}-2=0\implies \frac{x}{y}=\frac{-1\pm\sqrt{1+8}}{2}=1,-2$. Do as done in Solution 1 to get $9x^2+6xy+y^2=3x^2+4xy+Ky^2\implies 6x^2+2xy+(1-K)y^2=0\implies 6(\frac{x}{y})^2+2\frac{x}{y}+(1-K)=0\implies \frac{x}{y}=\frac{-2\pm \sqrt{4-24(1-K)}}{12}\implies \frac{x}{y}=\frac{-2\pm 2\sqrt{6K-5}}{12}=\frac{-1\pm \sqrt{6K-5}}{6}$. If $\frac{x}{y}=1$, then $1=\frac{-1\pm \sqrt{6K-5}}{6}\implies 6=-1\pm \sqrt{6K-5}\implies 7=\pm \sqrt{6K-5}\implies 49=6K-5\implies K=9$. If $\frac{x}{y}=-2$, then $-2=\frac{-1\pm \sqrt{6K-5}}{6}\implies -12=-1\pm \sqrt{6K-5}\implies -11=\sqrt{6K-5}\implies 121=6K-5\implies 126=6K\implies K=21$. Hence our final answer is $21\cdot 6=\boxed{126}$ -vsamc

See Also

2018 AIME I (ProblemsAnswer KeyResources)
Preceded by
Problem 4
Followed by
Problem 6
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15
All AIME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS